2007
DOI: 10.1529/biophysj.107.105528
|View full text |Cite
|
Sign up to set email alerts
|

Secondary and Tertiary Structure Elasticity of Titin Z1Z2 and a Titin Chain Model

Abstract: The giant protein titin, which is responsible for passive elasticity in muscle fibers, is built from approximately 300 regular immunoglobulin-like (Ig) domains and FN-III repeats. While the soft elasticity derived from its entropic regions, as well as the stiff mechanical resistance derived from the unfolding of the secondary structure elements of Ig- and FN-III domains have been studied extensively, less is known about the mechanical elasticity stemming from the orientation of neighboring domains relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 104 publications
1
54
0
1
Order By: Relevance
“…Biophysical characterization of constructs containing 2-6 domains revealed weak domain interactions through small interfaces, supporting the 'beads on a string' viewpoint. Prior to establishing the key role of the PEVK region in elasticity, Ig stretch-unfolding (later termed the secondary elasticity of titin; [8]) was thought to drive the mechanical response of titin. However, this is now a controversial concept and Ig stretch-unfolding is no longer regarded as a primary mechanism of titin elasticity in vivo [9,10].…”
Section: Historical View: Titin As the Sum Of Its Individual Domain Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Biophysical characterization of constructs containing 2-6 domains revealed weak domain interactions through small interfaces, supporting the 'beads on a string' viewpoint. Prior to establishing the key role of the PEVK region in elasticity, Ig stretch-unfolding (later termed the secondary elasticity of titin; [8]) was thought to drive the mechanical response of titin. However, this is now a controversial concept and Ig stretch-unfolding is no longer regarded as a primary mechanism of titin elasticity in vivo [9,10].…”
Section: Historical View: Titin As the Sum Of Its Individual Domain Cmentioning
confidence: 99%
“…Yet, a V-closure has only been observed in the crystal structure of Z1Z2, where it was stabilized by a crosslinking metal ion and co-existed with a conventional extended form ( Figure 1). An exhaustive study that used SAXS, NMR and MDS suggested that the closed conformation in Z1Z2 is rare and rapidly exchanges with the extended state [8,12]. The predominance of these extended arrangements probably stems from the fact that the integrating domains do not interact laterally with each other, so that V-conformations are not sustained in the absence of a stabilizing stimulus, e.g.…”
Section: Multi-domain Structures Reveal a Dynamic Higher Order In Thementioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are very long macromolecules with contour length larger than 1 mm [1], whose secondary structure is characterized by the presence of immunoglobulin (Ig) and fibronectin-type III (FNIII) domains, folded in forms of b-sheets, connected to the PEVK domain (rich in proline, glutamate, valine and lysine) [61]. At low forces, the elasticity is regulated by the tertiary structure and the (random coil) domain orientation, combined with the elasticity of PEVK domains [22,57,61]. At higher forces, the macromolecule response is dominated by an energetic competition of the entropic elasticity of the unfolded fraction of (Ig) and (FNIII) domains and by the enthalpic contribution of the folded !…”
Section: An Explicit Example: Titin Unfoldingmentioning
confidence: 99%
“…9,10 In these applications, the biomolecules that are conjugated onto nanoparticles can vary dramatically in size, with Stokes radii as small as 7 Å and as large as 1 lm, 11 and corresponding molecular weights ranging from <10 000 Da to >300 000 Da. Without a fluorescent label, it can be difficult to determine the tethering of these biomolecules to the particle surface, 12,13 and gold nanoparticles often quench fluorescence.…”
Section: Introductionmentioning
confidence: 99%